Weather Information, Tribune, KS 2024 - Amanda Burnett (Kansas Agricultural Experiment Station Research Reports, 2025)
Summary of 2024 weather for research conducted at the research locations included in the 2025 Western Kansas Agricultural Research report.
Keywords: Weather; precipitation; Tribune; Kansas; temperature; wind; evaporation